Influence of the Quality of Academic Information Systems (SIAKAD) and Service Quality on Student Satisfaction Faculty of Economics and Business Utp Surakarta - Dodik Khoirul Anam; Bayu Saputra Kurniawan; Zandra Dwanita Widodo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to address the academic and administrative problems of the Academic Information System (SIAKAD). This research uses quantitative techniques, analytical descriptive methodology, and collects primary data by sending online questionnaires through Google Form to UTP Surakarta students who are customers of SIAKAD services at the Faculty of Economics and Business. Meanwhile, secondary data for this study was collected from literature studies. The population of this study is 160 FEB students who are regular users of SIAKAD and are enrolled in one of the two study programs Bachelor of Management or Bachelor of Accounting. Proportional random sampling is the method used in the sampling procedure. Based on the research, student satisfaction at the Faculty of Economics and Business UTP Surakarta is strongly influenced by the quality of administrative services and SIAKAD.